PEMETAAN ZONASI TINGKAT KERAWANAN BANJIR BERBASIS SISTEM INFORMASI GEOGRAFIS KELURAHAN KLITREN, GONDOKUSUMAN, KOTA YOGYAKARTA - Nanda Melyadi Putri; Acep Muhamad Solehudin (Yayasan Nusantara Hasana Berdikari, 2026)
Klitren Village, located in Gondokusuman District, Yogyakarta City, is categorized as a flood-prone area, particularly during the rainy season. This study aims to map the flood vulnerability level in Klitren Village using a Geographic Information System (GIS) approach. Six parameters were analyzed to determine flood vulnerability: land elevation, slope, soil type, land use, rainfall, and river buffer. Both primary and secondary data were utilized and processed using ArcGIS 10.8 software. The analysis involved scoring, weighting, and overlaying the spatial parameters. The results show that the Klitren area is classified into three flood vulnerability zones: low, moderate, and high. The most influential parameters affecting flood vulnerability are land use and river buffer. The resulting flood vulnerability map is expected to serve as a reference for spatial planning and disaster mitigation efforts in densely populated urban areas such as Klitren Village.